How Legal Protection of Women in Home Workers Improving Family Welfare? - Sulistianingsih, Dewi; Prabowo, Muhammad Shidqon; Martitah, Martitah (Faculty of Law, Universitas Negeri Semarang, 2021)
Homeworkers are work that is done at home either on the basis of orders from others or doing on the basis of oneself. This type of work is referred to as informal workers, which is clearly difficult to obtain legal protection. Labor laws in Indonesia provide legal protection for both formal and informal workers, but the practice for informal workers is difficult to obtain legal protection. This program aims to describe and analyze the legal protections of women homeworkers in Semarang City in their efforts to make their families prosperous. This program uses socialization methods, interviews, observation and documentation. This program is conducted in the city of Semarang. The results of this program can be seen that the protection of homeworkers is still very minimal, especially for independent homeworkers. The implementation of statutory regulations has not been optimal, especially in manpower laws. The government is still not optimal in providing legal protection for informal workers, especially for homeworkers. Low wages, long working hours and the absence of health insurance are among the elements that homeworkers need to improve and increase in their efforts to make their families welfare. In the effort to achieve welfare for homeworkers' families, it is necessary to carry out supervision and guidance for homeworkers. Supervision and guidance can be carried out by the central government, local governments, non-governmental organizations, the academic community, observers of labor.